2002
DOI: 10.1038/sj.gt.3301682
|View full text |Cite
|
Sign up to set email alerts
|

Delayed delivery of AAV-GDNF prevents nigral neurodegeneration and promotes functional recovery in a rat model of Parkinson's disease

Abstract: Glial cell line-derived neurotrophic factor (GDNF) is a strong candidate agent in the neuroprotective treatment of Parkinson's disease (PD). We investigated whether adeno-associated viral (AAV) vector-mediated delivery of a GDNF gene in a delayed manner could prevent progressive degeneration of dopaminergic (DA) neurons, while preserving a functional nigrostriatal pathway. Four weeks after a unilateral intrastriatal injection of 6-hydroxydopamine (6-OHDA), rats received injection of AAV vectors expressing GDNF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
82
1

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(88 citation statements)
references
References 41 publications
5
82
1
Order By: Relevance
“…Alternatively, as a recent report showed that delivery of recombinant GDNF directly into the putamen of five Parkinson's disease patients in a phase I safety trial produced functional improvement, 25 gene transfer might allow long-term production of neuroprotective growth factors, thus resulting in a better outcome. 26 Indeed, gene therapy for Parkinson's disease in animal models also induced functional recovery using an AAV vector 27 or lentiviral vector, 28 although these vectors have several major problems such as immunogenicity. These diseases might be targeted using the microbubble-enhanced ultrasound method, as naked plasmid DNA is much safer and easier to handle.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, as a recent report showed that delivery of recombinant GDNF directly into the putamen of five Parkinson's disease patients in a phase I safety trial produced functional improvement, 25 gene transfer might allow long-term production of neuroprotective growth factors, thus resulting in a better outcome. 26 Indeed, gene therapy for Parkinson's disease in animal models also induced functional recovery using an AAV vector 27 or lentiviral vector, 28 although these vectors have several major problems such as immunogenicity. These diseases might be targeted using the microbubble-enhanced ultrasound method, as naked plasmid DNA is much safer and easier to handle.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, various factors including GDNF and VEGF have been shown to increase dopaminergic neuronal survival and promote survival and axonal growth in animal models of PD. [9][10][11] In addition to those factors, we and others have reported a potential therapeutic strategy using hepatocyte growth factor (HGF). [12][13][14][15][16][17][18][19] HGF acts as a neurotrophic and survival factor for embryonic motor neurons.…”
Section: Introductionmentioning
confidence: 99%
“…To date, most gene therapeutic approaches to PD have involved AAV-mediated transgene delivery to the striatum, the target projection area of nigral dopaminergic neurons. Indeed, the striatum has been the prime site for vector delivery in PD therapies aiming at dopamine restoration through expression of dopamine-synthesizing enzymes in striatal neurons (During et al, 1998;Wang et al, 2002;Eberling et al, 2008;Christine et al, 2009;Jarraya et al, 2009;Muramatsu et al, 2010;Valles et al, 2010), and also in gene therapeutic approaches involving neurotrophic factors such as glial cell-derived neurotrophic factor (GDNF) or neurturin (Kordower et al, 2000;Eslamboli et al, 2005;Eberling et al, 2009;Marks et al, 2010). The protective effect of neurotrophic factors released by transduced striatal neurons relies on their uptake by dopaminergic fibers in the striatum and retrograde axonal transport to the cell soma in the SNpc.…”
mentioning
confidence: 99%